Seller Responsibilities in Digital Transactions on the Shopee Marketplace System at the Trendy You Outfit Store - Ningrum, Ika Sulistya; Ismi, Hayatul; Musliadi, Ricki (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The huge potential in the electronic commerce (e-commerce) business cannot be separated from the development of internet users and the growth of the internet in Indonesia. The forms and interactions of e-commerce business actors in Indonesia are divided into various types, Shopee is a type of Online Marketplace Provider (OMP) e-commerce, apart from the profits that can be obtained from online shopping, there are also risks that may occur when the wrong goods are sent by the wrong party. seller and delays in delivery of goods. This research was conducted on one of the Shopee marketplaces, namely the Trendy You Outfit store, whether the responsibilities implemented by the Shopee marketplace have been implemented by the Trendy You Outfit store. The aim of this thesis research is first, how to carry out Shopee's marketplace responsibilities. second, how to resolve disputes at the trendy you outfit shop. The type of research is sociological legal research, namely research carried out on actual conditions or real conditions that occur in society. This research uses primary data originating from field data and secondary data consisting of primary, secondary and tertiary legal materials. The data collection technique used in this research is using unstructured interview methods and literature review. This research uses qualitative methods, namely research procedures that produce descriptive data, namely what is stated in writing. The research results show that the implementation of responsibilities at the Trendy You Outfit store in the Shopee marketplace has not yet been implemented. As a consumer, in accordance with the provisions of law number 8 of 1999 concerning consumer protection, article 4 letters b and h, the right to receive compensation, compensation and/or replacement is explained if the goods and/or services received are not in accordance with the agreement or are not as they should be. There needs to be legal protection, both preventive and repressive, for consumers if the seller's responsibilities to consumers are not fulfilled. And experienced losses from the consumer side and losses from sellers which had the impact of reducing interest in purchasing goods.